Rising of Chinese Blue Water Navy and American Hegemony In Asia Pacific - Agung Imam Zulhatta (Andalas Institute of International Studies, 2022)
Currently, China is growing into a new maritime power in the world. This country is listed with the largest number of commercial vessels with over 1,000 gross tons. The port of Shanghai has also transformed into one of the busiest ports globally, rivaling the Port of Amsterdam in terms of total cargo volume. China's shipping industry currently occupies the third position in the world. The maritime industry is increasingly competitive to ensure stable economic performance, but on the other hand, it is still highly dependent on secure access to markets and resources, particularly iron and fossil fuels. Taking into account the condition of the Chinese Navy and the government's Chinese Efforts to become a new maritime power in the world, China is currently trying to establish itself to realize its dream, namely the ability to become a force in blue water navy order to seize the United States' Hegemony in the Asia Pacific Region.